Structural Learning in Autistic and Non-Autistic Children: A Replication and Extension. - Oestreicher, Svenja; Bowler, Dermot M.; Derwent, Claire T.; Gaigg, Sebastian B.; Roessner, Veit; Vetter, Nora; Volk, Theresia; Beyer, Nicole; Ring, Melanie (Journal of Autism & Developmental Disorders, 2026)
The hippocampus is involved in many cognitive domains which are difficult for autistic individuals. Our previous study using a Structural Learning task that has been shown to depend on hippocampal functioning found that structural learning is diminished in autistic adults (Ring et al., 2017). The aim of the present study was to examine whether those results can be replicated in and extended to a sample of autistic and non-autistic children. We tested 43 autistic children and 38 non-autistic children with a subsample of 25 autistic and 28 non-autistic children who were well-matched on IQ. The children took part in a Simple Discrimination task which a simpler form of compound learning, and a Structural Learning task. We expected both groups to perform similarly in Simple Discrimination but reduced performance by the autism group on the Structural Learning task, which is what we found in both the well-matched and the non-matched sample. However, contrary to our prediction and the findings from autistic adults in our previous study, autistic children demonstrated a capacity for Structural Learning and showed an overall better performance in the tasks than was seen in earlier studies. We discuss developmental differences in autism as well as the role of executive functions that may have contributed to better than predicted task performance in this study.